2020
DOI: 10.3389/fcell.2020.587961
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 and mTOR Reciprocally Regulate Macrophage Phagolysosome Formation and Acidification Against Vibrio vulnificus Infection

Abstract: The marine bacterium Vibrio vulnificus causes potentially fatal bloodstream infections, typically in patients with chronic liver diseases. The inflammatory response and antibacterial function of phagocytes are crucial for limiting bacterial infection in the human hosts. How V. vulnificus affects macrophages after phagocytosis is unclear. In this report, we found that the bactericidal activity of macrophages to internalize V. vulnificus was dependent on mammalian target of rapamycin (mTOR) and NODlike receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…Previous studies revealed that V. vulnificus infection resulted in apoptosis and autophagy in the macrophages ( Kashimoto et al., 2003 ; Song et al., 2016 ). NLRP3 and mTOR signaling also is required for phagolysosome formation in the macrophages after V. vulnificus infection ( Huang et al., 2020 ). Our data suggested that overactivation of mTORC1 in the macrophages promoted the caspase 3 cleavage and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that V. vulnificus infection resulted in apoptosis and autophagy in the macrophages ( Kashimoto et al., 2003 ; Song et al., 2016 ). NLRP3 and mTOR signaling also is required for phagolysosome formation in the macrophages after V. vulnificus infection ( Huang et al., 2020 ). Our data suggested that overactivation of mTORC1 in the macrophages promoted the caspase 3 cleavage and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our research suggests that in addition to neutrophil activity, there may also be obstacles to the signaling transduction pathways in ALD mice, which may affect the immune response and the elimination of bacteria V. vulnificus . Besides, the NLR signaling is crucial for V. vulnificus infection, the absence of NLRP3 in macrophages impaired V. vulnificus -induced phagosome acidification and phagolysosome formation, leading to a reduction of intracellular bacterial clearance ( 46 , 47 ). In our study, we found that the number of DEGs related to the NLR signaling pathway was reduced in ALD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mechanism of sCD83 on DCs was detected. mTORC1 is a critical regulator for cell metabolism of DCs [26] and it regulates the activation and function of DCs including IL-1β and IL-18 production [37][38][39], so the expression of mTORC1 and p-mTORC1 were detected in sCD83 or CD83 + B cells treated DCs. sCD83 treatment reduced the expressions of mTORC1 and p-mTORC1 in activated DCs (Figure 4d).…”
Section: Scd83 Regulated the Cell Metabolism And Activation Of Dcs By...mentioning
confidence: 99%